Modest Propositional Contents in Non-Human Animals - Danon, Laura (2022)
Philosophers have understood propositional contents in many different ways, some of them imposing stricter demands on cognition than others. In this paper, I want to characterize a specific sub-type of propositional content that shares many core features with full-blown propositional contents while lacking others. I will call them modest propositional contents, and I will be especially interested in examining which behavioral patterns would justify their attribution to non-human animals. To accomplish these tasks, I will begin by contrasting modest propositional contents with primitive feature-placing contents: a kind of content that, according to some philosophers, can explain the behavior of non-human animals. I will examine which cognitive abilities are involved in having mental states with each of these contents and which sorts of behavioral patterns would provide evidence that an animal has one of them or another. Finally, I will present some empirical evidence which strongly suggests that some non-human animals have mental states with modest propositional contents.